Investigation of the physical, optical, and photocatalytic properties of CeO2/Fe-doped InVO4composite - Jindaporn Chaison (2018)
© 2017 Elsevier Ltd The CeO 2 /Fe-doped InVO 4 composites with various Fe concentrations (0.5, 1.0, 2.0, 5.0 and 6.0 mol%) was synthesized by homogeneous precipitation and hydrothermal methods. The as-synthesized samples were characterized by powder X-ray diffraction (XRD), Brunauer Emmett and Teller (BET)-specific surface area, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), and UV–visible diffuse reflectance spectroscopy (DRS). Fe-doping into InVO 4 crystal induces the distortion of the crystalline structure, the transformation of InVO 4 morphology, and the new energy subband level generation of Fe between the CB and VB edge of InVO 4 . The electron excitation from the VB to Fe orbitals results in the decreased band gap and the extended absorption of visible-light, and thus enhances its photocatalytic performance. Visible-light-driven photocatalytic degradation of Rhodamine B (RhB) dye in water was used to evaluate the photocatalytic performance of CeO 2 /Fe-doped InVO 4 composites. The results revealed that there is an optimum Fe (5.0 mol %) doping level. The composite with the optimum doping level obtains high photocatalytic activity of CeO 2 /Fe-doped InVO 4 composite compared to pure CeO 2 and pure InVO 4 host. The increase of photocatalytic activity of CeO 2 /Fe-doped InVO 4 composite was ascribed to the surface area, crystal defect, and band gap energy. Moreover, the photocatalytic enhancement is also because iron ions act as a trapping site, which results in the higher separation efficiency of photogenerated electrons and holes pairs in the CeO 2 /InVO 4 composite. The evaluation of radical scavengers confirmed that hydroxyl radical was the main active species during the photodegradation of RhB. These synergistic effects are responsible for the enhanced photocatalytic activity of CeO 2 /Fe-doped InVO 4 composite. Furthermore, the possible enhanced photocatalytic mechanism of the CeO 2 /Fe-doped InVO 4 composite was also proposed based on the calculation of band position.